2003
DOI: 10.1056/nejmoa023141
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Hodgkin's Lymphoma after Infectious Mononucleosis

Abstract: A causal association between infectious mononucleosis-related EBV infection and the EBV-positive subgroup of Hodgkin's lymphomas is likely in young adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
253
2
13

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 372 publications
(276 citation statements)
references
References 13 publications
8
253
2
13
Order By: Relevance
“…Contradicting the delayed-exposure hypothesis in our data for young adults are the risk of EBV-positive HL with lower birth order and the lack of association with self-reported IM, a clinically evident expression of infection delayed past childhood. For IM, the null finding resembles that of Sleckman et al 11 for EBV-positive early-stage HL but differs markedly from the case-control results of Alexander et al, 14 who found self-reported IM to be strongly associated with HL irrespective of EBV status, and from the cohort results of Hjalgrim et al, 15 who demonstrated a similar, 3-fold elevated risk of EBVpositive HL but no increase for EBV-negative HL in serologically confirmed IM patients.…”
Section: Discussioncontrasting
confidence: 62%
See 3 more Smart Citations
“…Contradicting the delayed-exposure hypothesis in our data for young adults are the risk of EBV-positive HL with lower birth order and the lack of association with self-reported IM, a clinically evident expression of infection delayed past childhood. For IM, the null finding resembles that of Sleckman et al 11 for EBV-positive early-stage HL but differs markedly from the case-control results of Alexander et al, 14 who found self-reported IM to be strongly associated with HL irrespective of EBV status, and from the cohort results of Hjalgrim et al, 15 who demonstrated a similar, 3-fold elevated risk of EBVpositive HL but no increase for EBV-negative HL in serologically confirmed IM patients.…”
Section: Discussioncontrasting
confidence: 62%
“…The inconsistencies of our findings with the delayed-exposure etiologic model for HL and with other published findings [11][12][13][14][15] have several possible explanations. (i) The proportion of HL tumors that are EBV-positive has been shown to vary markedly with the composition of the patient population.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Population‐based studies have demonstrated a positive association between infectious mononucleosis and cHL 60. However, this does not necessarily implicate EBV in the aetiology of cHL.…”
Section: Discussionmentioning
confidence: 95%